PHYTOCHEMICAL ANALYSIS AND ANTIMICROBIAL ACTIVITY OF ARTOCARPUS HIRSUTUS: AN IN VITRO STUDY - VINAY SUVARNA M N,; VENKATACHALAPATHY R,; MAKARI HANUMANTHAPPA K,; RAMESH B S, (International Journal of Pharma and Bio Sciences, 2014)
In the present study effort was aimed to evaluate phytochemical components and antimicrobial activity of Artocarpus hirsutus edible fruit part with different organic solvent extracts by Soxhlet extraction method with analytical grade solvents viz., methanol and petroleum ether. This study reports the potent phytochemical components which were observed qualitatively. The in vitro antimicrobial activity was performed by agar well diffusion method against the clinically important bacterial strains viz., Staphylococcus aureus (NCIM 2492), Bacillus subtillis (NCIM 2439) and Klebsiella pneumoniae (NCIM 2719) with the concentration of different extracts ranged from 25 to 75µL. It has shown the concentration dependent antimicrobial activity. This study reveals the presence of phytochemical components like alkaloids, flavonoids, saponins, terpenoids. The study shows the effective antimicrobial activity against Staphylococcus aureus and Klebsiella pneumoniae bacterial strains with maximum zone of inhibition compared with standard drug tetracycline